2017
DOI: 10.11648/j.jfa.20170504.12
|View full text |Cite
|
Sign up to set email alerts
|

Tax Information, Administration and Knowledge on Tax Payers’ Compliance of Block Moulding Firms in Ekiti State

Abstract: This study examined the impact of tax information, administration and knowledge on tax payers' compliance of Block Moulding Firms in Ekiti State, Nigeria using a survey research design. The data obtained from questionnaire were analysed using the ordinary least square regression method. The results showed that tax information and knowledge had positive significant impacts on tax compliance while tax administration had an insignificant impact on tax compliance with unstandardized beta coefficients of 0.251 (t =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…The results of this study are also consistent with previous research results (Adiasa, 2013;Saad, 2014;Ananda, 2015;Andreas & Savitri, 2015;Nurhayati, Halimatusadiah, & Diamonalisa, 2015;Agustiningsih & Isroah, 2016;Ilhamsyah, Endang, & Dewantara, 2016;Oladipupo & Obazee, 2016;Redae & Sekhon, 2016;Olaoye, Ayeni-agbaje, & Alaran-Ajewole, 2017). Nevertheless, there are researchers who find different results, the understanding of taxation is not proven to have a positive effect and significant against taxpayer compliance (Andinata, 2015).…”
Section: The Effect Of Tax Understanding On Taxpayer Compliancesupporting
confidence: 90%
“…The results of this study are also consistent with previous research results (Adiasa, 2013;Saad, 2014;Ananda, 2015;Andreas & Savitri, 2015;Nurhayati, Halimatusadiah, & Diamonalisa, 2015;Agustiningsih & Isroah, 2016;Ilhamsyah, Endang, & Dewantara, 2016;Oladipupo & Obazee, 2016;Redae & Sekhon, 2016;Olaoye, Ayeni-agbaje, & Alaran-Ajewole, 2017). Nevertheless, there are researchers who find different results, the understanding of taxation is not proven to have a positive effect and significant against taxpayer compliance (Andinata, 2015).…”
Section: The Effect Of Tax Understanding On Taxpayer Compliancesupporting
confidence: 90%
“…It is not an easy task to persuade taxpayers to comply with tax requirements even as the tax laws are not always precise in some respects (James & Alley, 2004). Olaoye et al (2017) concluded that the level at which taxpayers comply with tax laws in terms of filing returns and remittance are determined by their level of knowledge and information on tax administration in respect to tax rates, allowance, allowable and non-allowable expenses and penalty for tax default. The theoretical approaches of tax compliance have commonly been divided into economic deterrence theory and the wider behavioral theory (Frey & Feld, 2002).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Tax knowledge is recognized as one of the important elements influencing tax compliance behavior Olatunji Olaoye, 2017). XXXThe ability to understand taxation regulations by taxpayers is called tax knowledge (Ayuba et al, 2016).…”
Section: The Dynamics Of Tax Knowledgementioning
confidence: 99%